Transcendence and the secular - Hrabovecký, Pavol (Bogoslovni vestnik, 2025)
Secularism is one of those contemporary phenomena to which there are contradictory theological responses in the West: from negative and critical to positive and accepting. Writer Jon Fosse in his literary works describes the secular world as in need of transcendence. Thus, his literature offers at least the possibility of a dialogue between the secular and the transcendent. Fosse’s works resonate theologian John Milbank’s vision of secularism as a theological heresy. This study explores the shared principles of theological and literary perspectives of Fosse and Milbank and argues that literature is important contemporary locus theologicus and a common ground for dialogue between religion and the secular.
Keywords: contemporary theology; critique; dialog; dialogue; Fosse, Jon; književnost; kritika; literature; Milbank, John; secular; sekularizem; sodobna teologija; transcendent; transcendentno